1998
DOI: 10.1002/(sici)1097-4644(19981201)71:3<449::aid-jcb13>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin-like growth factors I and II and their binding proteins in human bone marrow stromal cells by dexamethasone

Abstract: Glucocorticoids inhibit the proliferation, but induce the differentiation, of bone marrow stromal cells into osteoblast-like cells. The mechanisms, however, are still conjectural. Since insulin-like growth factors (IGFs) have profound effects on osteoblast growth and differentiation, it is possible that glucocorticoids exert their effects on bone marrow stromal cells in part via regulation of IGFs. Therefore, we analyzed the effects of dexamethasone (Dex) on the expression of IGF I and IGF II in cultured preos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 51 publications
1
33
1
1
Order By: Relevance
“…My finding that Dex markedly inhibited IGF-I expression is consistent with the known inhibitory effect of Dex on IGF-I expression in several osteoblastic cell models. For example, Dex was observed to inhibit IGF-I expression in cultured rat bone cells [7] and human bone marrow stromal cell cultures [8], and also to have an adverse effect on IGF-I-mediated signaling of osteoblast differentiation in hMSC cells [16]. In addition, by contrast to the anabolic effect of IGF-I on bone, in vivo exposure to excessive glucocorticoids results in rapid bone loss with an increase in osteoporotic fracture risk [17].…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…My finding that Dex markedly inhibited IGF-I expression is consistent with the known inhibitory effect of Dex on IGF-I expression in several osteoblastic cell models. For example, Dex was observed to inhibit IGF-I expression in cultured rat bone cells [7] and human bone marrow stromal cell cultures [8], and also to have an adverse effect on IGF-I-mediated signaling of osteoblast differentiation in hMSC cells [16]. In addition, by contrast to the anabolic effect of IGF-I on bone, in vivo exposure to excessive glucocorticoids results in rapid bone loss with an increase in osteoporotic fracture risk [17].…”
Section: Discussioncontrasting
confidence: 86%
“…The effects of GCs have been studied on other members of the IGF/IGFBP system. For example, it has been reported that Dex can induce IGF-II at both the mRNA and protein levels in human mesenchymal stem cells (hMSC) during osteoblast differentiation [8], and the expression of IGFBP-2 was shown to be regulated by Dex in osteoblastic cell cultures in a positive [29] or negative manner [30]. However, I could not detect any changes in the mRNA expression levels of IGF-II or IGFBP2 in NIH3T3 cells treated either with Dex alone or in combination with 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations